Cognitive assessment of very preterm infants at 2-year corrected age: performance of the Italian version of the PARCA-R parent questionnaire. - Cuttini, Marina; Ferrante, Pierpaolo; Mirante, Nadia; Chiandotto, Valeria; Fertz, Mariacristina; Dall'Oglio, Anna Maria; Coletti, Maria Franca; Johnson, Samantha (Early Hum Dev, 2012)
BACKGROUND: Serial assessments of cognitive and language development are recommended for very preterm children, but standardized neuropsychological testing is time-consuming and expensive, as well as tiring for the child. AIMS: To validate the Italian version of the PARCA-R parent questionnaire and test its clinical effectiveness in assessing cognitive development of very preterm children at 2 years of corrected age. METHODS: 120 consecutive Italian very preterm children (mean gestational age 28.8 weeks, standard deviation 2.1) were assessed in four hospitals through the Mental Development Index (MDI) of the Bayley Scales of Infant Development (BSID-II). Parents completed the PARCA-R questionnaire, designed to measure children's non-verbal and verbal (vocabulary and sentence complexity) cognitive level. The correlation between the MDI and the PARCA-R Parent Report Composite (PRC) was tested through the Pearson correlation coefficient, and the receiver operating characteristic (ROC) curve was used to identify optimal PRC cut-offs. RESULTS: Significant correlation between the PRC score and MDI (r=0.60, p<0.001) indicated good concurrent validity. The area under the ROC curve was 0.83, and the cut-off of 46 lead to 72.7% sensitivity and 77.1% specificity in identifying children with moderate/severe cognitive delay (MDI<70). Negative predictive value was 96.6 (90.3-99.3). Screening through PARCA-R would reduce the number of children with MDI≥70 undergoing BSID-II or equivalent standardized tool from 109 to 25. CONCLUSIONS: The Italian version of PARCA-R retains good discriminative power for identifying cognitive delay in 2-year very preterm children. It is well accepted by parents, and represents a valid and efficient alternative for developmental screening and outcome measurement.
Keywords: Cognition; Female; Humans; Infant; Infant, Newborn; Infant, Premature; Italy; Male; Parents; Questionnaires; ROC Curve